One-pot sequential multicomponent reaction between in situ generated aldimines and succinaldehyde: facile synthesis of substituted pyrrole-3-carbaldehydes and applications towards medicinally important fused heterocycles. Issue 28 (24th April 2018) - Singh, Anoop; Mir, Nisar A.; Choudhary, Sachin; Singh, Deepika; Sharma, Preetika; Kant, Rajni; Kumar, Indresh
Abstract : An efficient sequential multi-component method for the synthesis of N -arylpyrrole-3-carbaldehydes has been developed. Abstract : An efficient sequential multi-component method for the synthesis of N -arylpyrrole-3-carbaldehydes has been developed. This reaction involved a proline-catalyzed direct Mannich reaction-cyclization sequence between succinaldehyde and in situ generated Ar/HetAr/indolyl-imines, followed by IBX-mediated oxidative aromatization in one-pot operation. The practical utility of this procedure is shown at gram-scale and the synthesis of diverse bioactive fused heterocyclic scaffolds such as pyrroloquinoline, pyrrolo-oxadiazole, dihydro pyrroloquinoline, and pyrrolo-phenanthridine.